Paralelisme Politik Media dalam Pemberitaan Pemilu 2014 di Indonesia - Simarmata, Salvatore (Jurnal ILMU KOMUNIKASI, 2017)
Media biases may caused by various factors. One of them is called political parallelism. Political parallelism weakens the roles of media in democratic process by becoming overly one-sided leading to low quality of news news quality. The aim of this article is to investigate the presence and effect of media political parallelism on election news during the 2014 legislative and presidential elections in Indonesia, using content analysis on news items from four print media outlets. The findings show that media with certain political parallelism display high favorability in coverage of its own affiliations.